Assessing the adoption and economic and environmental impacts of Brachiaria grass forage cultivars in Latin America focusing on the experience in Colombia. Final Technical Report prepared for the CGIAR Standing Panel on Impact Assessment - Labarta, Ricardo Antonio; Martínez, Jose Maria; Yaccelga, Angie; Reyes, Byron A.; Gomez, Lorena; Maredia, Mywish K.; DeYoung, David; Carriazo, Fernando; Toro, Mariana (2017)
Brachiaria grasses are native to Africa but were introduced to the Americas in the early 50’s due to its easy adaptation to the region and high potential productivity in livestock production systems (Miles, Maass, & do Valle, Brachiaria: biology, agronomy and improvement, 1996). A considerable expansion of Brachiaria grasses has been reported in various countries of Latin-America, especially in Brazil (Instituto Brasileiro de Geografia e Estatística, 2007; Jank, Barrios, do Valle, Simeão, & Alves, 2014; Landers, 2007). Brachiaria Decumbens cv. Basilisk was the first adopted cultivar in Latin-American and remains in current times as one of the important grass forage cultivars in the region.